The Impact of Parenting Patterns, Waste Management, and Sanitation Facilities on Stunting - M. Ainul Fikrih; Firdawsyi Nuzula; Roshinta Sony Anggari (Poltekkes Kemenkes Surabaya, 2025)
Indonesia is still facing serious nutritional problems, with stunting being a major problem that has a significant impact on children's physical and cognitive development. This research aims to identify the influence of parenting patterns, waste management, and sanitation facilities. Sanitation facilities regarding stunting incidents in Wonoasri Village, Tempurejo District, Jember Regency. Methodology used is quantitative analytical correlation research with a cross-sectional study approach. Samples are taken sequentially or successively from the population over a certain period until the desired sample size is reached; the period for this research is one month. Data were analyzed using the Chi-Square statistical test for bivariate analysis and ordinal logistic regression for multivariate analysis. The results of the bivariate analysis showed that the highest incidence of stunting was very short, with 81 cases (62%). Statistically, there is a significant correlation between parenting style with p value=0.017, waste management p value=0.000, and sanitation facilities p value=0.017 with the incidence of stunting. Multivariate analysis shows that waste management significantly negatively influences nutritional status, with p value of 0.000 and OR 29.168; sanitation facililities OR 3.823; and parenting OR 1.926. These results indicate that the prevalence of stunting is strongly influenced by inadequate waste management and reduces the possibility of better nutritional status. Local government efforts to reduce stunting prevalnces rates by improving sanitation with the community-based total sanitation program, because stunting problem is caused by multifactorial so the role of the community is very important.